2012
DOI: 10.1038/bjc.2012.495
|View full text |Cite
|
Sign up to set email alerts
|

EGFR pathway biomarkers in erlotinib-treated patients with advanced pancreatic cancer: translational results from the randomised, crossover phase 3 trial AIO-PK0104

Abstract: Background:We aimed to identify molecular epidermal growth factor receptor (EGFR) tissue biomarkers in pancreatic cancer (PC) patients treated with the anti-EGFR agent erlotinib within the phase 3 randomised AIO-PK0104 study.Methods:AIO-PK0104 was a multicenter trial comparing gemcitabine/erlotinib followed by capecitabine with capecitabine/erlotinib followed by gemcitabine in advanced PC; primary study end point was the time-to-treatment failure after first- and second-line therapy (TTF2). Translational analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 31 publications
3
56
0
Order By: Relevance
“…Later on, Boeck et al (2013) confirmed Ueno's results in some aspect analyzing tissue biomarkers in pancreatic cancer patients treated with the anti-EGFR agent erlotinib, and showed that K-ras wild-type status was associated with improved overall survival, while no significant correlation was found for EGFR-immunohistochemical analysis, EGFR-FISH, PTENimmunohistochemical analysis, intron 1 or exon 13 R497K polymorphism.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Later on, Boeck et al (2013) confirmed Ueno's results in some aspect analyzing tissue biomarkers in pancreatic cancer patients treated with the anti-EGFR agent erlotinib, and showed that K-ras wild-type status was associated with improved overall survival, while no significant correlation was found for EGFR-immunohistochemical analysis, EGFR-FISH, PTENimmunohistochemical analysis, intron 1 or exon 13 R497K polymorphism.…”
Section: Discussionsupporting
confidence: 66%
“…These difficulties can be attributed to the remarkable genomic heterogeneity of PDAC combined with a usually small size of patient cohorts, which have restricted the effective and efficient mining of the data. In particular, lack of targeted molecular agents for the significantly altered genes in PDAC call into question the effectiveness of some of the applied methods of data analysis, and indicate the importance of using approaches that are suitable for dealing with patient heterogeneity and the subtyping of patient population (Boeck et al, 2013;Kindler et al, 2011;Moore et al, 2007;Van Cutsem et al, 2004. Evolution-based biomedical constructs, including parsimony phylogenetics, have been shown to be a suitable tool for dealing with heterogeneous and highdimensional data such as gene expression microarray (AbuAsab et al, 2008b(AbuAsab et al, , 2011Abu-Asab et al, 2013;Sarnat and Netsky, 1984;Wiley, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The mutational status of KRAS and EGFR gene copy numbers, evaluated in 117 and 107 patients enrolled on the NCIC CTG PA.3, were not predictive of a survival benefit in patients receiving the combination of gemcitabine/ erlotinib (24). Contrary to this, in the AIO-PK0104 study, a multicenter trial comparing gemcitabine/erlotinib followed by capecitabine with capecitabine/erlotinib followed by gemcitabine in advanced pancreatic cancer, KRAS wild-type status was associated with improved survival (HR =1.68, P=0.005) in patients treated with erlotinib (25). Another post hoc analysis of the AIO-PK0104 study correlated the biomarker data on KRAS exon 2 mutation status with objective response to 1st-line therapy and with OS after start of 2nd-line chemotherapy.…”
Section: Targeting Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 79%
“…In Lee's [14] work, the drug (erlotinib) used is indeed known as an EGFR-target compound. Erlotinib is a small molecule that is able to block the signal transduction downstream of EGFR, such as the PI3K-AKT or the RAS-RAF-MAPK-MEK-ERK pathway [3]. In our experiment, however, AKT was ranked the fifth from the bottom, meaning the signals transmitted to AKT were not blocked.…”
Section: Drug Effects Identification By In Silico Simulation Of Protementioning
confidence: 94%